Direct association of Bloom’s syndrome gene product with the human mismatch repair protein MLH1 - Pedrazzi, Graziella (Oxford University Press, 2001)
Bloom’s syndrome (BS) is a rare genetic disorder characterised by genomic instability and cancer susceptibility. BLM, the gene mutated in BS, encodes a member of the RecQ family of DNA helicases. Here, we identify hMLH1, which is involved in mismatch repair (MMR) and recombination, as a protein that directly interacts with BLM both in vivo and in vitro, and that the two proteins co-localise to discrete nuclear foci. The interaction between BLM and hMLH1 appears to have been evolutionarily conserved, as Sgs1p, the Saccharomyces cerevisiae homologue of BLM, interacts with yeast Mlh1p. However, cell extracts derived from BS patients show no obvious defects in MMR compared to wild-type- and BLM-complemented BS cell extracts. We conclude that the hMLH1–BLM interaction is not essential for post-replicative MMR, but, more likely, is required for some aspect of genetic recombination.